2010
DOI: 10.1111/j.1442-9071.2009.02182.x
|View full text |Cite
|
Sign up to set email alerts
|

Resurgence of Acanthamoeba keratitis in Auckland, New Zealand: a 7‐year review of presentation and outcomes

Abstract: AK has become significantly more common in New Zealand in the current decade. This study highlights the fundamental importance of early diagnosis and appropriate management in ensuring favourable outcomes. Practitioners should maintain a clinical suspicion of AK, especially as 96% of the subjects in this study were contact lens wearers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
7
17
0
Order By: Relevance
“…The low average incidence of 2 per year in our study is similar to studies where an outbreak has not been reported, both in Australia11 12 and in other countries such as New Zealand,7 Hong Kong,9 Japan14 and USA (Cleveland4 and Philadelphia3), where the number of cases has ranged from 1.5 per year to 3.6 cases per year. Melbourne’s clean water could account for the low incidence of AK; Melbourne has some of the highest quality drinking water in the world where great care is taken to disinfect water sources via chlorination, chloramination and ultraviolet irradiation 15.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The low average incidence of 2 per year in our study is similar to studies where an outbreak has not been reported, both in Australia11 12 and in other countries such as New Zealand,7 Hong Kong,9 Japan14 and USA (Cleveland4 and Philadelphia3), where the number of cases has ranged from 1.5 per year to 3.6 cases per year. Melbourne’s clean water could account for the low incidence of AK; Melbourne has some of the highest quality drinking water in the world where great care is taken to disinfect water sources via chlorination, chloramination and ultraviolet irradiation 15.…”
Section: Discussionsupporting
confidence: 88%
“…Epidemiological data of AK has been described over the past decade in various countries such as the USA,3 4 England,5 India,6 New Zealand7 and Singapore 8. The wide range in incidence (1.5 per year9 to 31 cases per year10) is thought to be due to the variability in type and frequency of CL use, contamination of domestic and swimming pool water, the amoebicidal efficacy of CL cleaning solutions and availability of diagnostic techniques for AK 2 6.…”
Section: Introductionmentioning
confidence: 99%
“…Cases of AK without a history of contact lens wear or trauma are rare, with a recent New Zealand study reporting 96% of AK cases are associated with contact lens wear and 4% are associated with trauma. [2] Indeed, the annual incidence of AK is approximately two cases per million in the New Zealand population,[2] indicating a low probability that the second infection was new and unrelated.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Numerous studies have highlighted the importance of early diagnosis in ensuring favorable outcomes in AK, however, there are little published data regarding the recurrence rate, the long-term excysting effect of corticosteroid in the acute phase, or the effects of reintroduction of topical corticosteroids years after the acute event. [234]…”
Section: Introductionmentioning
confidence: 99%
“…The number of affected individuals is increasing worldwide. Morever, recent outbreaks of Acanthamoeba keratitis have been recently reported in the United States and Australia (Verani et al, 2009;Tu and Joslin, 2010;Patel et al, 2010;Joslin et al, 2010). AK is an acute, painful infection that can occur in immunocompetent individuals.…”
Section: Central Nervous Systems Infections Due To Free Living Amoebaementioning
confidence: 99%